Aspects of user profiles that can improve mobile augmented reality usage - Sanches, Silvio Ricardo Rodrigues; Oizumi, Marcio; Oliveira, Claiton; Damasceno, Eduardo Filgueiras; Sementille, Antonio Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Augmented Reality (AR) applications running on mobile devices have become more popular in recent years. As with digital games, many developers have begun to direct their applications to mobile platforms, although the processing power of these devices is usually smaller when compared to the computing power of laptops and desktops. Applications developed for computing devices, including mobile devices, typically have a well-defined target audience, and some of them use AR technology. The use of AR can actually add value to the application, but despite the additional motivation, interaction in this type of environment may be more complex compared to traditional applications. Considering this context, the main objective of the present work is to identify which key aspects in the user profile impact the design of mobile AR applications.
Keywords: Augmented Reality; Mobile Device; User Profile